Hubungan Antara Motivasi Masuk Pg-Paud Dengan Prestasi Belajar Mahasiswa Pg-Paud FKIP UMS Angkatan 2013 - Astuti, Tri Puji (2016)
The purpose of this research is to know the correlation about motivation go to PG-PAUD with achievement student PG-PAUD FKIP UMS grade 2013. The research design is descriptive correlational. Population of this research is 48 student and the sample is 40 student, disproportionate stratified random sampling is the method. Collection teachniques such as documentasion and questionnaire. This research use correlation product moment for the analysis method. The result is r product moment= 0,667 and sig= 0,000 (p<0,05). It means that this is a positive correlation and this correlation is significant. Therefore hypothesis which reads the correlation about motivation go to PG-PAUD with achievement student PG-PAUD FKIP UMS grade 2013 accepted. It means there is positive correlation significant characteristic between motivation go to PG-PAUD with achievement student.